Heat stress inhibits expression of the cytokines, and NF-κB-NLRP3 signaling pathway in broiler chickens infected with salmonella typhimurium. (May 2021) - Tang, Lu-Ping; Li, Wei-Hao; Liu, Yi-Lei; Lun, Jian-Chi; He, Yong-Ming
Abstract: High ambient temperature has potential influence on oxidative stress, or systemic inflammation affecting poultry production and immune status of chickens. Heat stress (HS) induces intestinal inflammation and increases susceptibility of harmful pathogens, such as Salmonella and Escherichia coli . Intestinal inflammation is a common result of body immune dysfunction. Therefore, we designed an experiment to analyze the effects of 35 ± 2 °C HS on salmonella infection in chickens through regulation of the immune responses. 40 broiler chickens were randomly divided into 4 groups: control group, heat stress (HS) group, salmonella typhimurium (ST) group and model group (heat stress +  salmonella typhimurium, HS + ST). Birds in HS and model group were treated with 35 ± 2 °C heat stress 6 h a day and for 14 continuous days. Then, ST and model group birds were orally administrated with 1 mL ST inoculum (10 9  cfu/mL). Chickens were sacrificed at the 4th day after ST administration and ileum tissues were measured. We observed that heat stress decreased ileum TNF-α and IL-1β protein expressions. Concomitantly heat stress decreased NLRP3 and Caspase-1 protein levels. The protein expressions of p–NF–κB-p65 and p-IκB-α in ileum. Heat stress also inhibited IFN-α, p-IRF3 and p-TBK1, showing a deficiency in the HS + ST group birds. Together, the present data suggested that heat stress suppressed intestinal immune activity in chickens infected by salmonella typhimurium, as observed by the decrease of immune cytokines levels, which regulated by NF-κB-NLRP3 signaling pathway. Highlights: High ambient temperature affected poultry production and immune status of chickens. Heat stress (HS) induces intestinal inflammation and increases susceptibility of harmful pathogens, such as Salmonella and Escherichia coli. This study aim to analyze the effects of 35 ± 2 °C HS for 14 continuous days on ileum morphology, immune parameters related to intestinal immune functions in chickens infected with Salmonella typhimurium. The interesting results found that heat stress suppressed intestinal immune activity in salmonella typhimurium infected chickens through down-regulating NF-κB-NLRP3 signaling pathway.